A Glaciological Map of a Small Ice Shelf (Hell’s Gate Ice Shelf, Terra Nova Bay, Antarctica) - BONDESAN, ALDINO (Brigati e Glauco, 1997)
4th International Conference on Geomorphology, Bologna, 28 agosto-3 settembre 1997